The first flight of the OLIMPO experiment: instrument performance. (May 2020) - Presta, G; Ade, P A R; Battistelli, E S; Castellano, M G; Colantoni, I; Columbro, F; Coppolecchia, A; Alessandro, G D'; Bernardis, P de; Gordon, S; Lamagna, L; Masi, S; et al.
Abstract: OLIMPO is a balloon-borne experiment aiming at spectroscopic measurements of the Sunyaev-Zel'dovich effect in clusters of galaxies. The instrument operates from the stratosphere, so that it can cover a wide frequency range (from ∼ 130 to ∼ 520 GHz in 4 bands), including frequencies which are not observable with ground-based instruments. OLIMPO is composed of a 2.6-m aperture telescope, a differential Fourier transform spectrometer and four arrays of lumped element kinetic inductance detectors operating at the temperature of 0.3 K. The payload was launched from the Longyearbyen airport (Svalbard Islands) on July 14th, 2018, and operated for 5 days, at an altitude of 38 km around the North Pole. We report the in-flight performance of the first lumped element kinetic inductance detector arrays ever flown onboard a stratospheric balloon.